100 Triaging Two Week Wait Referrals According to ABS Guidelines Established During the COVID-19 Pandemic Is Safe Practice. (19th August 2022) - Sadik, N; Rutherford, C; Ledwidge, S; Johnson, L
Abstract: Aim: CoVid-19 has affected healthcare globally, disrupting cancer care. Two weeks wait (2ww) breast cancer referrals were triaged according to Association of Breast Surgery (ABS) guidelines with patients with no red flag symptoms deemed low risk and able to be discharged back to their GP. This study aimed to assess the safety and efficacy of implementing these guidelines. Method: A database was established to prospectively collect 2ww breast cancer referrals from the outset of CoVid-19. Two Consultants triaged the referrals and if there was disagreement, a third Consultant arbitrated. Data were recorded for patient age, gender, presenting complaint, assessment, investigations, diagnosis, and outcome and also time from initial referral to discharge letter to the GP. Results: 188 patients were referred via the 2ww pathway to St Bartholomew's Hospital from 22/03/2020 to 08/04/2020. 43 (22.9%) were discharged with a median age of 34 (22–83 years) at the time of referral. The mean time from referral receipt to response was 12.1 (0 – 60 days). 15 (34.9%) patients were subsequently re-referred. Mean time from re-referral to one-stop clinic assessment was 9.1 (2 – 22 days), in keeping with NICE two week wait criteria. Of the patients re-referred, all patients underwent imaging in the form of mammogram and/or ultrasound scan. No patients were found to have pre-invasive or invasive disease. Conclusions: Triaging patients based on GP referrals is a safe way of streamlining low risk patients. This has the potential to become standard practice worldwide but requires larger multi-centre studies prior to implementation.